Ups and downs in finance, ups without downs in inequality - Olivier Godechot; Nils Neumann; Paula Apascaritei; István Boza; Martin Hällsten; Lasse Folke Henriksen; Are Hermansen; Feng Hou; Jiwook Jung; Naomi Kodama; Alena Křížková; Zoltán Lippényi; et al. (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2021)
The upswing in finance over the past several decades has led to rising inequality, but do downswings in finance lead to a symmetric decline in inequality? In this paper, we analyze the asymmetry of the effect of ups and downs in financial markets, as well as the effect of increased capital requirements and the bonus cap on national earnings inequality. We use administrative employer-employee linked data on earnings from 1990 to 2017 for twelve countries. Additionally, we use data on earnings from bank reports, from 2009 to 2017 in thirteen European countries. We find a strong asymmetry in the effects of financial ups and downs on earnings inequality, a mitigating effect of rising capital requirements on the contribution of finance to inequality, and a restructuring effect of the bonus cap for the earnings of financiers, while neither policy affects absolute levels of earnings inequality.
Keywords: N2; D31; G38; 330; inequality; finance; financial crisis; regulation